Transparency or Opacity (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
The datafication and digitalisation of business models and decision-making processes have led to calls for more transparency, but at the same time question of suitable concepts to address these issues are raised. The contributions collected in this volume, which address various areas of law, examine from a jurisprudential perspective whether and under what conditions transparency should or can be granted and to what extent already existing transparency concepts can be successfully implemented. They are all contributions to the discussion of the 2nd Conference of the Research Network Young Digital Law, which took place on 22 and 23 July 2022 at the University of Hamburg. With contributions by Marco Billi, Dr. Jonas Botta, Dr. Gordian Konstantin Ebner, Jun.-Prof. Dr. Elena Freisinger, Joris Krijger, Dr. Tobias Mast, Dr. Juliane Mendelsohn, Paul Nolan, Jun.-Prof. Alessandro Parenti, Kostina Prifti, Dr. Patrick Raschner, Dr. Christopher Rennig, David Schneeberger, Prof. Dr. Evert Stamhuis, Tamara Thuis and Prof. Dr. Thomas Wischmeyer.